Research cafés: how libraries can build communities through research and engagement. (19th September 2018) - Stephan, Katherine
The Research Support Team at Liverpool John Moores University (LJMU) runs events called research cafés throughout the academic year. During these cafés, we bring together PhD students, early career researchers and more established academics over lunch to give them an opportunity to talk about their work to a lay audience of their peers and the public. From its inception in 2013 we have maintained the overall format of the research café, based as it is on promoting interdisciplinary dialogue in an informal setting, while also making a few small but significant changes. These changes have in turn increased the visibility and reach of research promotion within the Library. Against that backdrop, this article – which is based on a lightning talk and poster session presented at the 41 st UKSG Annual Conference, Glasgow, in April 2018 – will outline why the library is ideally placed to facilitate this type of scholarship sharing and why research and community engagement should be viewed as an integral part of a university library's agenda. It will also discuss how its success has allowed our Team to work in partnership with colleagues from across the University in new and exciting ways. Finally, it will address what further developments we can make to continue to improve and help the research community at LJMU and beyond.